A study on fine Nbss/γ-(Nb, X)5Si3 eutectic with significantly improved room-temperature fracture toughness by added ZrB2. (November 2022) - Chen, Dezhi; Wang, Qi; Chen, Ruirun; Wang, Shu; Su, Yanqing; Fu, Hengzhi
Abstract: Four NbSi based ultrahigh temperature alloys with compositions of Nb-16Si-20Ti-1ZrC- x ZrB2 ( x = 0, 0.5, 1, 3) (at.%) were prepared by vacuum non-consumable arc melting. The microstructure evolution, fracture toughness, and fracture behavior of four alloys were investigated. Results showed that four alloys consisted of Nbss, γ-(Nb, X)5 Si3, and (Nb, X)3 Si phases. The low content of ZrB2 facilitates the disintegration of (Nb, X)3 Si, while the high content of ZrB2 stabilizes (Nb, X)3 Si. The maze-like Nbss/γ-(Nb, X)5 Si3 eutectic structure forms in Nb-16Si-20Ti-1ZrC-0.5ZrB2 alloy. With the increase of ZrB2 content, the room-temperature fracture toughness of Nb-Si-Ti-ZrC-based alloy increases and decreases. When the addition amount of ZrB2 is 0.5 at.%, the room-temperature fracture toughness is the largest of 18.4 MPa·m 1/2, and the fracture mode changes from quasi-cleavage fracture to dimple fracture. Compared with the base alloy, it is increased by 28%. It is the highest value of as-cast arc melting that has been reported so far. The maze-like eutectic of the high content of Nbss (54.9 ± 5.9%) phase promotes the formation of microcracks and inhibits the propagation of cracks in Nb-16Si-20Ti-1ZrC-0.5ZrB2 alloy. Highlights: The maze-like Nbss/γ-(Nb, X)5 Si3 eutectic structure forms in Nb-16Si-20Ti-1ZrC-0.5ZrB2 alloy. Fracture toughness was increased to 18.4 MPa·m 1/2 by addition of 0.5% ZrB2 . The Nb-16Si-20Ti-1ZrC-0.5ZrB2 alloy is a ductile dimple fracture.